Animal movement network analysis as a tool to map farms serving as contamination source in cattle cysticercosis - Aragão, Samuel C. [UNESP]; Ito, Pier K.R.K. [UNESP]; Paulan, Silvana C. [UNESP]; Utsunomyia, Yuri T. [UNESP]; Filho, José H.H. Grisi; Nunes, Cáris M. [UNESP] (FapUNIFESP (SciELO), 2017)
Bovine cysticercosis is a problem distributed worldwide that result in economic losses mainly due to the condemnation of infected carcasses. One of the difficulties in applying control measures is the identification of the source of infection, especially because cattle are typically acquired from multiple farms. Here, we tested the utility of an animal movement network constructed with data from a farm that acquires cattle from several other different farms to map the major contributors of cysticercosis propagation. Additionally, based on the results of the network analysis, we deployed a sanitary management and drug treatment scheme to decrease cysticercosis' occurrence in the farm. Six farms that had commercial trades were identified by the animal movement network and characterized as the main contributors to the occurrence of cysticercosis in the studied farm. The identification of farms with a putative risk of Taenia saginata infection using the animal movement network along with the proper sanitary management and drug treatment resulted in a gradual decrease in cysticercosis prevalence, from 25% in 2010 to 3.7% in 2011 and 1.8% in 2012. These results suggest that the animal movement network can contribute towards controlling bovine cysticercosis, thus minimizing economic losses and preventing human taeniasis.
Keywords: Animal movement network; Cattle; Cysticercosis; Disease control; Taenia saginata; Traceability